Evaluation Bias and its Control* - Michael Scriven (The Evaluation Center at Western Michigan University, 2011)
Originally published as Paper #4, Occasional Paper Series, June, 1975 *A paper originally written in conjunction with The Evaluation Center's Grant # GW-7903 from the National Science Foundation.